Review of Qawaid Fiqhiyyah in the Practice of Bapapai in the Indigenous People of Dayak Bakumpai - Muhammad Yasin (Syntax Idea)
Customary law has long been in force in Indonesia. Regarding marriage, customary law views it as an important event in public life, because marriage does not only concern the bride and groom, but also both parents of both parties, siblings and even their respective families. Not only that, marriage is a very meaningful event and one that fully receives attention and is followed by the spirits of the ancestors of both parties. The results of this study show that the bapapai tradition when viewed from its philosophical value is in the form of efforts made by the Bakumpai community to Allah swt. so that the marriage ceremony can run smoothly and the household that is built is blessed with sakinahan and convenience in all aspects is 'urf shahih because the customs carried out by the Bakumpai Dayak community do not contradict a shari'i proposition or do not justify something that is forbidden. This is in line with the rules of fiqh "al-adat muhakkamah". While in some processions such as myths about bad luck or disaster if you leave the tradition of bapapai and pinsit is 'urf fasid. But if society is able to change its perception that the only one who can provide protection to humans is Allah Almighty. Merely then it can change the category to 'urf shahih". This is in accordance with the rules of fiqh "al-umur bimaqashidiha